2008
DOI: 10.1143/jpsj.77.111010
|View full text |Cite
|
Sign up to set email alerts
|

Solid 4He and the Supersolid Phase: from Theoretical Speculation to the Discovery of a New State of Matter? –A Review of the Past and Present Status of Research–

Abstract: The possibility of a supersolid state of matter, i.e., a crystalline solid exhibiting superfluid properties, first appeared in theoretical studies about forty years ago. After a long period of little interest due to the lack of experimental evidence, it has attracted strong experimental and theoretical attention in the last few years since Kim and Chan (Penn State, U.S.A.) reported evidence for nonclassical rotational inertia effects, a typical signature of superfluidity, in samples of solid 4 He. Since this '… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…In recent years, much experimental and theoretical effort has been devoted to understanding the low-temperature physical nature of solid pure 4 He, largely stimulated by the claimed observation of superfluidity [1]. The most recent consensus view indicates that the anomalies observed in the non-classical rotational inertia, shear modulus and the specific heat are not due to superfluidity of the ideal commensurate solid, but rather they must be related to vacancies and other intrinsic defects such as grain boundaries or dislocations, or extrinsic factors such as the 3 He impurity level [2]. Defects of a similar nature have been invoked to explain a phenomenon called the geyser effect, observed in the expansion of solid 4 He through a small orifice into vacuum under constant source pressure (P 0 ) and temperature (T 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much experimental and theoretical effort has been devoted to understanding the low-temperature physical nature of solid pure 4 He, largely stimulated by the claimed observation of superfluidity [1]. The most recent consensus view indicates that the anomalies observed in the non-classical rotational inertia, shear modulus and the specific heat are not due to superfluidity of the ideal commensurate solid, but rather they must be related to vacancies and other intrinsic defects such as grain boundaries or dislocations, or extrinsic factors such as the 3 He impurity level [2]. Defects of a similar nature have been invoked to explain a phenomenon called the geyser effect, observed in the expansion of solid 4 He through a small orifice into vacuum under constant source pressure (P 0 ) and temperature (T 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 This experimental result attracted considerable interest and served as a starting point for many theoretical and experimental works. 7 Thus far, considerable information about the phenomenon of supersolidity has been obtained. The observed NCRIf decreases with an increase in the driving velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The values of ϕ (±L/2) at the boundaries are determined by A(x) and J through (11). This setup describes a system attached to a current generator (one can regard this onedimensional system as an orifice attaching two reservoirs of superfluids or supersolids; see, e.g., Sec.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Although the possibility of supersolids was discussed theoretically about 40 years ago, 1-3 extensive and intensive studies started since Kim and Chan reported [4][5][6][7] the first evidence for nonclassical rotational inertia 3 in a solid phase of 4 He in torsional oscillator experiments. Subsequently, experimental studies have revealed various puzzling properties of supersolid 4 He: [8][9][10][11] the enhancement of elasticity having the same temperature dependence as the resonance frequency shift, 12 the sensitivity of the resonance frequency shift to the history of the annealing process 13 and to small concentrations of 3 He, 12 superflow along the grain boundaries, 14 and ultraslow relaxation dynamics in the dissipation and resonance frequency shift in the torsional oscillator experiments. 15 As a consistent explanation of these experimental results, several theories have been proposed, such as defectmediated superfluidity mechanisms, 16,17 a nonsuperfluid glass picture, 18,19 and intrinsic supersolidity of the defect-free crystal.…”
Section: Introductionmentioning
confidence: 99%